Enhancing Social Value through Orange Technology Adoption in Creative Industry Micro Enterprises - Ninda Lutfiani; Hindriyanto Dwi Purnomo; Heru Riza Chakim; Syahrul Mu’Arif Wahid; Oliver Sauntos (ADI Publisher, 2025)
Social media–based digital transformation has become an essential strategy for MSMEs to expand their market reach and strengthen consumer loyalty in the digital economy era. This article presents a conceptual review and empirical synthesis of digital business transformation strategies in MSMEs that utilize social media as the core channel for marketing and customer service. By integrating the Technology Acceptance Model (TAM), Customer Engagement theory, and the Resource-Based View, this paper proposes a strategic framework consisting of (1) digital capabilities, (2) content and engagement, (3) digital after-sales services, and (4) a collaborative ecosystem (platforms and micro-influencers). The literature synthesis indicates that interactive social media activities and responsive services are consistently associated with increased customer engagement and brand loyalty among MSMEs. Practical recommendations and future research directions are provided to support MSMEs in implementing loyalty-oriented digital transformation.